'Categories We Share': Mobilising Common In‐groups in Discourse on Contemporary Immigration in Greece†. (5th October 2012) - Sapountzis, Antonis; Figgou, Lia; Bozatzis, Nikos; Gardikiotis, Antonis; Pantazis, Pavlos
ABSTRACT Prejudice reduction has been an important concern within social psychology both in theory and applied research. According to the premises of Social Identity Theory, redrawing of the category boundaries is often considered a necessary step in order to battle prejudice, because in‐group favouritism when the category boundaries change is diffused to the previously distinct identities. The present paper offers a review of the relevant research, and following a discourse analytic perspective argues that recategorisation can also be viewed as a rhetorical resource that people use in verbal interaction in order to achieve certain rhetorical ends. This point is exemplified using interview data from Greece with Greek participants who mobilise common in‐groups between themselves and the immigrants in Greece. Different common in‐groups were mobilised on the basis of common human nature, common ethnic descent and through the use of the common experience of migration that many Greek people have because Greece has been an emigrant sending country for the biggest part of the 20th century. Occasionally, these category constructions were used to differentiate between immigrants of different ethnic descent claiming that only certain immigrant groups can integrate to Greek society, whereas on other instances, these common in‐groups were used in order to inoculate speakers of accusations of prejudice. Copyright © 2012 John Wiley & Sons, Ltd.